Evaluating instructional coaching : people, programs, and partnership - Thomas, Sharon (English teacher); Knight, Jim; Harris, Michelle (English teacher); Hoffman, Ann (One Fine Bird Press ; ASCD, 2022)
"This book shows schools and school districts how to evaluate instructional coaching and covers the essential components of effective measurement, including: evaluation of individual coaches and coaching programs, recruiting and hiring effective coaches, and taking the right steps to retain coaches for sustained positive student outcomes over time"--